Web Page Ranking Algorithms Through Centrality Measures - Dash, Saroj Kumar; Jaganathan, B. (Journal of Informatics and Mathematical Sciences, 2017)
In this paper we give a brief overview of the adjacency matrix based page rank that we used in the Google search engine. In this paper various centrality measures discussed like in-degree centrality, out-degree centrality, degree centrality and Eigen centrality. We have applied the above mentioned centrality measures to web page ranking. This approach does not involve any iterative technique. This centrality measures are better than original iterative based page rank algorithm for ranking the web pages.